Phygital-Technologies as a Tool for Developing Efficient Communication with Today’s Customer - A. S. Melekhova (Вестник Российского экономического университета имени Г. В. Плеханова)
A key aspect of marketing strategy today is an ability to attract new generations of customers. The present day generation - digitalnatives (digital aboriginals, generation Z) is becoming a fast growing target group of consumer market and future global online-commerce. On the basis of Russian and overseas research on social – psychological and behavioral characteristics of generation Z the author studies the approach to building communication through which brands could broadcast their messages to customers and reveal their values. Phygital-technologies mean communications showing specificity, interests and preferences of generation Z, which provide an opportunity to create a new eco-system by using key advantages of traditional and digital tools. The new generation digitalnatives was born and grew up at the age of the Internet, gadgets and digital technologies. It is more useful to get in touch with this groupd through on-line platforms by developing a unique entertaining, laconic content, which could get within the eye-sight of Z-customers and comply with their interests and behavioral characteristics. However, the efficient two-sided communication implies not only on-line space, it includes off-line environment. The author shows that applying the approach, which could provide mutual integration of different channels of communication into a unique strategic system is an effective way of attracting the attention of new generations.